2014
DOI: 10.1007/s00167-014-3148-5
|View full text |Cite
|
Sign up to set email alerts
|

Lack of evidence to support present medial release methods in total knee arthroplasty

Abstract: V (expert opinion).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
40
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 64 publications
0
40
0
1
Order By: Relevance
“…Our findings might indicate that semimembranosus tendon was one of most important posteromedial stabilizers for maintaining the medial pivot motion during flexion even after TKA and that avoiding the substantial release led to better clinical outcomes. Hunt et al recently reviewed on extent of medial release in TKA for varus-type osteoarthritis that the classic extensive medial release might be unnecessary and might be associated with iatrogenic injury to the pes anserinus and saphenous nerve, instability and abnormal knee kinematics [30]. They added that minimal medial release might allow for improved soft tissue balancing leading ultimately to improved functional outcome [30].…”
Section: Discussionmentioning
confidence: 98%
“…Our findings might indicate that semimembranosus tendon was one of most important posteromedial stabilizers for maintaining the medial pivot motion during flexion even after TKA and that avoiding the substantial release led to better clinical outcomes. Hunt et al recently reviewed on extent of medial release in TKA for varus-type osteoarthritis that the classic extensive medial release might be unnecessary and might be associated with iatrogenic injury to the pes anserinus and saphenous nerve, instability and abnormal knee kinematics [30]. They added that minimal medial release might allow for improved soft tissue balancing leading ultimately to improved functional outcome [30].…”
Section: Discussionmentioning
confidence: 98%
“…In addition to the above mentioned studies, various and complex protocols of medial release have been reported [15][16][17][18][19]. Somewhat extensive release techniques can lead to complications such as instability and neurovascular injury [12]. Instability which leads to pain, walking difficulty, abnormal polyethylene wear, patellofemoral maltracking, and early loosening is still one of the major causes of TKA failure [6,[20][21][22].…”
mentioning
confidence: 98%
“…Even though medial soft tissue release has been accepted as an essential step for gap balancing, there exists a controversy in methods and the order of soft tissue release to achieve balanced gap during TKA of varus deformed osteoarthritic knee [8,[15][16][17][18][19][23][24][25]. There is still a lack of evidence supporting the current numerous medial release techniques for varus TKA [12]. At any rate, minimal and efficacious algorithmic release is the prerequisite of the ideal soft tissue balancing technique in TKA.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Second, there could be some overlap among the medial release steps because there is no definite boundary between medial soft tissue structures. However, this possibility seems to be minimal because the medial release technique used in our study was simplified to three steps compared with that used in previous studies [17,31]. Although there are numerous medial release techniques that differ in sequence and structures released, Hunt et al [17] noted that there is a lack of evidence supporting current methods.…”
Section: Discussionmentioning
confidence: 80%